On the fracture of the unidirectional composites in compression - Akbarov, SD; Sisman, T; Yahnioglu, N (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
The experimental studies of the fracture of unidirectional composite materials under loading along the reinforcing elements showed that one of the major mechanism of this fracture is the stability loss in material structure. Up to the present time, numerous theoretical and experimental investigations of the mentioned problems have been made. Note that in these investigations (carried out from a theoretical viewpoint), the problems considered have been studied in the framework of the Euler approach and those have been reduced to investigations of the corresponding eigenvalue problems. In the present paper, a method for investigating the problem of fracture (stability loss) of a unidirectional composite in compression has been given, which uses as a criterion the value of the compressive force for which the initial infinitesimal curvature given to the fibre or layer starts to increase and grows indefinitely. In these cases the investigations are carried out in the framework of the piecewise-homogeneous body model with the use of the exact three-dimensional non-linear equations of the deformable solid body mechanics. Note that the results obtained with the application of the proposed approach to the investigation of the mentioned fracture problems coincide with those which have been obtained in the framework of the Euler approach. Moreover, the approach is also employed successfully for the theoretical investigations of the problems of the fracture mechanics of composites in compression, where the study in the framework of the Euler approach are impossible. in the present paper the fracture (stability) problems of composites with viscoelastic components in compression are also studied by the use of the proposed approach. (C) 1997 Elsevier Science Ltd.
Keywords: CURVED LAYERS; Engineering